PELAKSANAAN UNDANG-UNDANG NOMOR 15 TAHUN 2014 DALAM PENETAPAN LABUNGKARI SEBAGAI IBUKOTA KABUPATEN BUTONTENGAH - WIRIDIN, DARMAWAN (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
The Law’s Observation Of Regulation Number 15th 2014 Related With The Establishment Of Labungkari as The Capital City Of Middle Buton Districk..The aim of this research is to find out the advisability of Labungkari as the Capital City of Middle Buton Districk observed from a law’s side and to find out a background, a weakness, and surplus of established Labungkari as the Capital City of Middle Buton Districk. This research was done in Labungkari, exactly in a government of Middle Button Districk.The method was applied in this research is the descriptive method and purposed to describe anything that have forms the background of establishment Labungkari as the Capital City Of Middle Buton Districk. The writer use a qualitative analysis based on a reports and a documentation in the field. A data collecting technique in this research includes by a profound interview and a secondary data and a tertiary data a study book, a document, and the articles.From the research, the writer concluded that the establishment Labungkari as the Capital City of Middle BurtonDistrict is not advisable because the establishment is not based on a mechanism that have permanently in a law and the establishment is just based on a collective consensus between a societies element.